Frequency of Urinary Tract Abnormalities on MCUG of Spina Bifida Occulta Patients with Urinary Complaints - Akhtar, Samina; Riaz, Ramish (Journal of Pediatric Neurology, 2017)
Spina bifida occulta (SBO) is usually considered as benign entity without having any clinical significance. In Pakistan, there is a lack of studies on spina bifida. Clinicians usually ignore the mild urinary complaints and do not look with the perspective of SBO background. Micturating cystourethrography (MCUG) of the 71 children with SBO having urinary complaints was done. Analysis was done via SPSS version 20. A total of 70.4% of the patients had urinary tract abnormalities on MCUG. Vesicoureteric reflux was the most common finding. SBO is a clinically significant disorder. Especially in patients with urinary complaints, MCUG must be done to look for underlying pathologies.
Keywords: spina bifida occulta; urinary tract abnormalities; vesicoureteric reflux; urinary complaints; nocturnal enuresis; MCUG